The Qishla of the city of Zakho an archaeological field study - Argushi, Dr. Yadgar Mohammed Saleem Argushi; Barzanji, L. Mehdi Jalal Mustafa Barzanji Mustafa; Bradosti, Prof.Dr. Zidan Rashid Khan Audal Bradosti (Sulaimani Journal for Humanities, 2025)
Zakhko Qishla is considered one of the most important archaeological sites within the city. Given that some parts of it have been preserved, it can be considered one of the archaeological and architectural testaments in the region. This study aims to be a comprehensive analysis of the site, examining its technical specifications and architectural origins. The building is still in use today and has undergone several maintenance and restoration efforts, though not always in accordance with academic and scientific standards.
Keywords: Qishla; Zakho; Bahdinan Emirate; Qishla planning; architectural elements; decorative elements